Working the past : narrative and institutional memory - Linde, C. (Charlotte) (Oxford : Oxford University Press, 2009)
'Working the Past' shows how stories that might otherwise be seen as part of mundane daily life are in fact essential to the formation and maintenance of individual and group identity. Her original research will appeal to those interested in narrative studies, linguistics, anthropology, sociology, and institutional memory.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Communication in organizations -- Case studies; Corporate culture -- Case studies; Corporate image -- Case studies; Knowledge management -- Case studies